Selfie sofa with flexible arrangement / Norashikin Kamarudin … [et al.] - Kamarudin, Norashikin; Abdul Latif, Nur Hannani; Ahmad Zaki, Junaiza; Zakaria, Shaikh Abdul Karim Yamani; Nik Hashim, Nik Hazlan; Hamzah, Norhayati (2015)
The selfie sofa with flexible arrangement concept furniture was chosen due to the current issue of maximizing the space in the living room wisely. This paper analysed a sofa innovation by producing multi-arrangement furniture that suits with human lifestyle, comfort, mobility and trend. The market questionnaire survey of the selfie sofa was carried out on 100 correspondences, categorized based on their gender, age and profession. More than 80% of the correspondences agreed and gave positive feedback on this product. The product focused on suitability of color and simplicity and flexibility of design, material used, suitability for small and large spaces, ergonomic, commercial value and expected price. By presenting the selfie sofa with flexible arrangement, this paper aimed to highlight the strengths and weaknesses of this product before it enters the market. Overall, the results showed the selfie sofa with flexible arrangement is a value added product.